2017
DOI: 10.3389/fmicb.2017.02104
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones and Beneficial Microbes: Essential Components for Plants to Balance Stress and Fitness

Abstract: Plants are subjected to various abiotic stresses, such as drought, extreme temperature, salinity, and heavy metals. Abiotic stresses have negative impact on the physiology and morphology of plants through defects in the genetic regulation of cellular pathways. Plants employ several tolerance mechanisms and pathways to avert the effects of stresses that are triggered whenever alterations in metabolism are encountered. Phytohormones are among the most important growth regulators; they are known for having a prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
244
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(311 citation statements)
references
References 141 publications
9
244
0
9
Order By: Relevance
“…Remarkably, the significantly higher t ‐Z concentration corresponded with zero RBD index in outside canopy position at week 6 and the lowest RBD susceptibility at week 9. Although no previous studies have investigated the effect of t ‐Z concentration on RBD of citrus fruit, it could be argued that high t ‐Z levels increases membrane integrity and, therefore, reduces RBD incidence …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, the significantly higher t ‐Z concentration corresponded with zero RBD index in outside canopy position at week 6 and the lowest RBD susceptibility at week 9. Although no previous studies have investigated the effect of t ‐Z concentration on RBD of citrus fruit, it could be argued that high t ‐Z levels increases membrane integrity and, therefore, reduces RBD incidence …”
Section: Resultsmentioning
confidence: 99%
“…Although no previous studies have investigated the effect of t-Z concentration on RBD of citrus fruit, it could be argued that high t-Z levels increases membrane integrity and, therefore, reduces RBD incidence. 19,47 In order to gain better insight on how the measured PGRs correlated with each other and with RBD incidence, the dataset of fruit from different canopy positions was subjected to PCA. The scores ( Fig.…”
Section: Incidence Of Rind Breakdown Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…PGP microorganisms use several mechanisms to stimulate drought tolerance in plants (Vurukonda et al ., ; Etesami and Maheshwari, ): (i) the microbial enzyme 1‐aminocyclopropane‐1‐carboxylate (ACC) deaminase contributes to control the concentration of the plant stress phytohormone ethylene, by degrading its precursor ACC (Glick, ); (ii) microorganisms contribute to modulate plant hormone homeostasis by producing auxin [i.e., indole‐3‐acetic acid (IAA)], cytokinins and giberellins. These phytohormones are involved in a wide range of adaptive responses and may determine changes in plant root gene expression and root architecture (Egamberdieva et al ., ; Lim and Kim, ); (iii) by manipulating the plant antioxidant system microorganisms decrease the reactive oxygen species (ROS) concentration (Wang et al ., ); (iv) the microbial release of osmolytes acts synergistically with those produced by the plant and enhances resistance to water stress (Etesami and Maheshwari, ); (v) exopolysaccharides produced by microorganisms recondition the root microenvironment by favouring water retention and protecting plant roots against desiccation (Rossi et al ., ); (vi) microorganisms contribute to enhance the plant induced systemic tolerance to drought by altering the host physiology and the metabolic processes (Cho et al ., ); (vii) an indirect effect of microbial activity is the solubilization of poorly available nutrients such as iron and phosphorus (Pii et al ., ). Interestingly, evidences suggest that the bacteria‐mediated protection is a drought‐activated mechanism (Rolli et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that the phyllosphere microbiome may change leaf wettability by producing hygroscopic particles (Beattie, 2011), changing cuticle permeability (Schreiber et al, 2005;Beattie, 2011;Ritpitakphong et al, 2016) leading to increases in cuticular transpiration (Schreiber et al, 2005). In terms of axis of plant defense, changes in plant traits, such as decreases in water potential and xylem conductivity (Beattie, 2011), stomatal closure or opening (Jones & Dangl, 2006;Friesen et al, 2011;Sawinski et al, 2013), biosynthesis of plant hormones, such as indole-3acetic acid (IAA), abscisic acid (ABA) and ethylene (Lindow & Brandl, 2003;Beattie, 2011;Egamberdieva et al, 2017), may either be defensive responses to pathogens or shifts promoted by them in order to increase their virulence and growth (Beattie, 2011). Consequently, such changes associated with plant defense may directly affect axes of leaf temperature, photosynthesis and hydraulics.…”
Section: Phyllosphere Traits As the Missing Link Among Axes Of Plantmentioning
confidence: 99%